STRATEGI KOMISI PEMILIHAN UMUM KABUPATEN BENGKALIS DALAM MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR PROVINSI RIAU TAHUN 2018-2023 - Hardiyanto, Ekky; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was motivated by the simultaneous election of regional heads of Riau Province for the third wave. In this election, the Central KPU targets Riau people's participation to reach 70%. However, in its implementation, it was only able to get 54% of the total votes from the 363,530 DPT in Bengkalis Regency. This makes Bengkalis Regency only ranked 10th out of 12 regencies / cities in Riau Province. This of course is not good news for the democratic system in Indonesia. This study aims to determine the strategy of the Bengkalis KPU in increasing the participation of strategic theory, political participation theory, political socialization theory. The writing method used in this thesis is qualitative. The types of data in this study are primary data and secondary data. Data collection techniques in this study were interviews and documentation. The data analysis technique used is descriptive qualitative.The results of this study indicate that the KPU's strategy is to increase public participation through: (1) Strengthening Strategies, efforts are made to increase the capacity and quality of the organizers of the election for Governors and Deputy Governors through technical guidance and improve communication and information disclosure through information boards, mass media, through mosque and smart home stakeholders. (2) Rationalization Strategy, the effort made is by socializing face to face communication such as going to campus, schools, ramadhan safaris and socializing various media such as Facebook, WhatsApp, KPU website of Bengkalis Regency, television, radio, newspapers, banners, billboards, leaflets and media props. (3) Persuasion strategies, conducting leisurely walks, roadshows, establishing stands at beach party festivals, and conducting interactive dialogues on radio and and television, of course with the assistance of the Riau Provincial KPU. (4) Confrontation strategy, in the form of socialization of how to vote and the disadvantages of not voting, the KPU invites the public to vote through a sermon in a mosque with the theme of choosing a leader. The supporting factors for the implementation of the Bengkalis KPU strategy are the availability of adequate human resources, professionalism, support from the government and stakeholders. Meanwhile, the inhibiting factors were limited funds, number of personnel, area, and lack of public response in socialization. The author concludes that the Bengkalis KPU has implemented these four strategies with the existing supporting factors. However, there are also several inhibiting factors that make this strategy less than optimal.